Thermal degradation of poly[2-(3-chloro-3-methylcyclobutyl)-2-hydroxyethyl methacrylate] - Coskun, M; Demirelli, K (Elsevier Sci Ltd, 1997)
The thermal degradation of poly [2-(3-chloro-3-methylcyclobutyl)-2-hydroxyethyl methacrylate] [poly(CBHEMA)] has been studied by using thermal volatilisation analysis (TVA) and thermogravimetry (TG). Programmed heating was carried out at 10 degrees C min(-1) from room temperature to 500 degrees C. Volatile products were separated by subambient TVA and identified by gasphase IR and MS, and CC-MS for volatile liquids. The cold ring fraction and partially degraded polymer have been examined by IR spectroscopy. The monomer was not formed during the degradation since HCl elimination from the chain began at about 150 degrees C, which is a low temperature for the production of monomer. However, some monomer homologues from the HCl-eliminated polymer were dedected as minor products. The polymer yields carbon monoxide, methane and oxygen as non-condensable products at -196 degrees C, Carbon dioxide, hydrogen chloride, water and some unsaturated and saturated hydrocarbons were found in the volatile products. The liquid products of the degradation, the formation of anhydride ring structures and the mechanism of degradation are discussed. (C) 1997 Elsevier Science Limited.
Keywords: Methyl-Methacrylate; Copolymers; Stability